Effect of nano silica and pretreated rubber on the properties of terminal blend crumb rubber modified asphalt. (30th December 2017) - Han, Lili; Zheng, Mulian; Li, Jinglong; Li, Yifeng; Zhu, Yueming; Ma, Qiang
Highlights: Nano silica enhanced high temperature property of terminal blend binder. NaClO solution pre treated crumb rubber improved binder property and compatibility. The proposed modified binder matched to SBS polymer modified binder (I-C). Treated rubber and nano modified binder held greater subzero creep compliance. Nano silica interacted physically rather than chemically in modification. Abstract: This research aimed to evaluate the physical and rheological properties of crumb rubber (CR) and nano silica modified asphalt. The wet process terminal blend (TB) CR-nano binders were prepared and characterized through a set of physical property tests and fluorescence microscopy, scanning electron microscopy as well as Fourier transform infrared spectroscopy techniques. Results indicate incorporation of nano silica into TB enhanced high temperature binder property but slightly reduced its low temperature ductility. However, by pre treating CR with sodium hypochlorite solution, the binder property and compatibility could be improved which was comparable to polymer modified bitumen. Additionally, nano-TB asphalt demonstrated enhanced dynamic modulus and decreased phase angle compared to TB, indicating its deformation resistance was increased. The bending beam rheometer test reveals rubber pre treating could increase the low temperature creep compliance of nano-TB binder. The microscopic images verified nano silica and CR grains were well dispersed in matrix asphalt, and several peaks disappeared whereas no silicon-related absorption was found in the spectrum of nano-TB binder, indicating the change in functional groups was probably caused by blending condition and nano silica barely interacted chemically with base bitumen or crumb rubber.